PROBLEMATIKA WAKAF ASET TANAH PERSYARIKATAN MUHAMMADIYAH DI SULAWESI SELATAN - Ambo Rappe (IAIN BONE, 2019)
AbstractThis study concerns the problem of Muhammadiyah waqf land assets in the province of South Sulawesi. The first problem is how to manage waqf land in Muhammadiyah organizations in South Sulawesi. Second, what efforts have been made in resolving the problem of Muhammadiyah waqf land assets in South Sulawesi.The type of research used is field research conducted at all Muhammadiyah Regional Leadership Offices in South Sulawesi province. Data was collected through interviews, collections, and observations. This study concludes that; First, the management of waqf land assets is still traditional, which is intended only for development activities and social activities. In fact, management has not run optimally. Therefore, it still needs cooperation between the Waqf Board and the Property with other parties in the management of waqf land assets so that they can run effectively and benefit. Second, the land assets are less pronounced and not aimed at the economic empowerment that only oriented to the devotional activities.Keywords: Waqf; Land Asset; Muhammadiyah.